Identification of chalcone isomerase gene family in Astragalus mongholicus revealed genes regulating isoflavone synthesis - Wang, Zhen; Wang, Panpan; Wang, Xinxin; Kong, Lingyang; Wu, Jianhao; Ren, Weichao; Liu, Xiubo; Ma, Wei (Frontiers in Plant Science, 2025)
Astragalus mongholicus (AM) is the original plant of the famous traditional Chinese medicine Astragali Radix, and its isoflavones are important bioactive substances with wide-ranging medicinal values. The chalcone isomerase (CHI) serves a pivotal function in flavonoid synthesis. However, the CHI gene family in AM has not yet been characterized and systematically analyzed. The present study identified a number of eight AmCHIs distributed on five chromosomes and classified them into four types. The evolutionary relationships, conserved motifs, gene structures, and cis-elements of AmCHIs are discussed. The transcriptome revealed the expression profiles of the AmCHI genes in roots, stems and leaves. In order to characterize AmCHIs function, recombinant proteins AmCHI3, AmCHI4 and AmCHI5 were expressed in Escherichia coli, and the enzyme activity assay showed that the typeI AmCHI4 could only catalyze naringenin chalcone to chalcone, and the typeII AmCHI3 catalyzed the conversion of naringenin chalcone to chalcone and of isoliquiritigenin to Liquiritigenin. Type III AmCHI5 lacked catalytic activity. In addition, gene suppression of AmCHI3 was carried out by using antisense oligodeoxynucleotides (AsODN). Transient gene silencing of AmCHI3 decreased the contents of calycosin, calycosin-7-glucoside and formononetin. indicating that AmCHI3 gene has a positive regulatory effect on the synthesis of isoflavonoids in AM. These results provide the data support for future elucidation of the regulatory mechanism of CHI in isoflavone biosynthesis.